Complicated Acute Appendicitis during COVID-19 Pandemic: The Hidden Epidemic in Children - Delgado-Miguel, Carlos; Muñoz-Serrano, Antonio J.; Miguel-Ferrero, Miriam; De Ceano-Vivas, María; Calvo, Cristina; Martínez, Leopoldo (European Journal of Pediatric Surgery, 2021)
Introduction Since home confinement for novel coronavirus disease 2019 (COVID-19) pandemic began, pediatric visits to the emergency department (ED) have decreased, including consultation for abdominal pain. Our aim is to investigate the incidence of complicated acute appendicitis (AA; peritonitis or appendicular mass) during confinement for COVID-19 pandemic and to compare it with the previous 5 years.Materials and Methods A retrospective study was performed in children with AA who underwent surgery between March 9 and April 13 from 2015 to 2020; patients were divided into six groups according to the year of surgery. We analyzed demographic variables, time from onset of symptoms, mean hospital stay, cumulative incidence, and incidence rate of complicated appendicitis.Results A total of 168 patients were included with no differences in the number of patients, gender, and age between groups. Patients in 2020 (COVID-19 group) presented longer symptom progression time (46.8 hours; p = 0.046), higher rate of complicated appendicitis (48.4%; p = 0.004), longer mean hospital stay (4.9 days; p < 0.001), increased cumulative incidence (8.27 cases per 100,000 children per 0.1 years; p < 0.001), and increased incidence rate of complicated appendicitis (83 cases per 100,000 children; p < 0.001) when compared with other groups.Conclusion Delayed ED visit of children with AA during home confinement lead to an increased rate of complicated appendicitis. It is crucial to make parents aware of the importance of early diagnosis and treatment of abdominal pain.
Keywords: SARS-CoV-2; COVID-19; perforated appendicitis; peritonitis; children